2020
DOI: 10.1093/cid/ciaa653
|View full text |Cite
|
Sign up to set email alerts
|

The Penicillin Allergy Delabeling Program: A Multicenter Whole-of-Hospital Health Services Intervention and Comparative Effectiveness Study

Abstract: Background Penicillin allergies are associated with inferior patient and antimicrobial stewardship outcomes. We implemented a whole-of-hospital program to assess the efficacy of inpatient delabeling for low-risk penicillin allergies in hospitalized inpatients. Methods Patients ≥ 18 years of age with a low-risk penicillin allergy were offered a single-dose oral penicillin challenge or direct label removal based on history (dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 30 publications
6
84
0
Order By: Relevance
“…Many patients can be de-labelled without the need for penicillin challenges, associated with reduced broad-spectrum antimicrobial use, and this strategy should be encouraged in patients admitted to hospital with COVID-19 in advance of a potential need for antimicrobials. 23 Furthermore, we identified frequent use of broad-spectrum empirical therapy (β-lactam–β-lactamase inhibitors) for lower respiratory tract infections, empirical escalation from piperacillin–tazobactam to carbapenems in critical care, and preferential use of carbapenems over carbapenem-sparing alternatives. These findings all represent tractable targets for antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Many patients can be de-labelled without the need for penicillin challenges, associated with reduced broad-spectrum antimicrobial use, and this strategy should be encouraged in patients admitted to hospital with COVID-19 in advance of a potential need for antimicrobials. 23 Furthermore, we identified frequent use of broad-spectrum empirical therapy (β-lactam–β-lactamase inhibitors) for lower respiratory tract infections, empirical escalation from piperacillin–tazobactam to carbapenems in critical care, and preferential use of carbapenems over carbapenem-sparing alternatives. These findings all represent tractable targets for antimicrobial stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, rates of true allergic reactions to penicillins have been shown to be far less than previously reported [ 32 ]. Chua and colleagues conducted a multicenter, prospective study to evaluate rate of penicillin allergy delabeling following review by trained nursing, pharmacy, or medical staff using a validated assessment tool [ 16 ]. Based on risk stratification, patients were directly delabeled, offered oral penicillin challenge, or referred for outpatient allergy assessment.…”
Section: Resultsmentioning
confidence: 99%
“…This study suggests that there is a population of hospitalized patients in Scotland with a reported penicillin allergy who are suitable for our PADL process delivered via appropriately trained clinical teams. Several larger studies have shown similar success with direct de‐labelling approaches based on allergy history alone 8,9 and/or oral challenge tests 9,10 . Further work is needed to provide a standardized approach for training and to map out the roles of various staff in the process to provide an efficient process utilizing the skills of medical, nursing and pharmacy staff while ensuring professional liability is considered.…”
Section: Figurementioning
confidence: 99%